Pseudo-anévrysme artériel post traumatique: à propos de deux cas. - TRAORE Ousmane; DIARRA Ouncoumba; SANOGO Souleymane; KOUMA Alassane; KEITA Adama Diama, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2020)
A pseudoaneurysm or false aneurysm is a small pocket of blood communicating with an artery or a heart cavity and secondary to the rupture of the wall of the latter. The blood is then contained by the adjacent structures. It is distinguished from the aneurysm, the latter retaining the integrity of its wall. We report two cases of false aneurysms of different topography diagnosed in the radiology department of the AUGUST 20 hospital in CASABLANCA in order to describe the role of imaging. They were two patients, one aged 24, stabbed in the left thigh and the other 21, traumatized by a glass bottle in the left temporal area. They presented with a painful, non-pulsatile mass in the left thigh for the first case and pulsatile for the second. Ultrasound and CT angiography were used to confirm the diagnosis by specifying the exact